2021
DOI: 10.1177/2040622321998860
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of coronavirus 2019 infection in patients with chronic kidney disease: a systematic review and meta-analysis

Abstract: Background: Information on coronavirus disease 2019 (COVID-19) infection in patients with chronic kidney disease (CKD) remains limited. To understand the influence of COVID-19 infection in patients with pre-existing CKD, we conducted a systematic review and meta-analysis to evaluate and compare the risks of all-cause mortality, hospitalization, and critical progression between patients with and without CKD. Methods: We selected randomized controlled trials (RCTs), prospective or retrospective observational, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In fact, once COVID-19 disease is established, CKD patients have high mortality rates because the disease severely affects their already impaired kidney function [ 4 ]. These figures consistently underscore the high vulnerability of CKD patients to COVID-19, related to multiple factors [ 26 , 27 ], and the need to protect this segment of the population.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In fact, once COVID-19 disease is established, CKD patients have high mortality rates because the disease severely affects their already impaired kidney function [ 4 ]. These figures consistently underscore the high vulnerability of CKD patients to COVID-19, related to multiple factors [ 26 , 27 ], and the need to protect this segment of the population.…”
Section: Discussionmentioning
confidence: 80%
“…vulnerability of CKD patients to COVID-19, related to multiple factors [26,27], and the need to protect this segment of the population. Another way to look at the COVID-19 death toll on CKD patients is to examine the excess mortality.…”
Section: Plos Onementioning
confidence: 99%
“…The advanced age and multiple comorbidities often prevalent in CKD patients might place these patients at higher risk of critical illness. A meta-analysis of the literature also demonstrated that patients with CKD alone had an increased association with all-cause mortality compared with those without CKD [ 13 ]. Data from a global health research network called TriNetX (Cambridge, MA) showed that the incidence of hospitalization, ventilation and mortality (risk ratios 1.4–1.5, 1.5–2.0 and 1.4–1.8, respectively) for COVID-19 were all higher in CKD patients than in those without CKD, even after enrolling KT patients [ 14 ].…”
Section: Covid-19 Pandemic and Ckd: The Higher Incidence Of Critical Illness And Acute Kidney Injury In Patients With Ckdmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic significantly affected individuals suffering from chronic medical conditions, such as chronic kidney disease (CKD), in terms of risk of infection, morbidity, and mortality [ 1 ]. Individuals suffering from CKD were reported to be at high risk of COVID-19 infection due to their dependence on in-center dialysis treatment, which is a high-risk environment for the transmission of COVID-19 infection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%